The representation of migrants in the mainstream and critical news media - Yidiz, Ilkay; Tanyildizi, Nural Imik (IGI Global, 2024)
Migration is a phenomenon that has existed since the beginning of human history. The migrations in history were made for such climatic differences, finding better food, and living in more suitable places. However, in the last few centuries, migrations have been mostly carried out for purposes such as wars, conflicts, and adaptation to the new world order. Turkey is a country exposed to migration due to wars in neighboring countries. This study tried to reveal how issues such as migration, immigrants, and refugees, which are considered important problems all over the world in both mainstream and critical news media.The research population consists of all digital newspapers published in Turkey. In this study, Hürriyet, Sabah, and Yenişafak newspapers, such as Cumhuriyet, Evrensel, and Sözcü newspapers, were selected as samples to represent the mainstream media. The news about immigrants in the selected newspapers was examined using the discourse analysis method. © 2024 by IGI Global. All rights reserved.